NEW SOLUTION OF ELECTROMAGNETIC LAUNCHER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper presents the design, simulation, and experimental validation of a linear alternative current actuator. From this point of view, the main purpose of the paper is to analyze the working principle of the linear actuator and to explain how electromagnetic and mechanical parameters can modify the force produced by this device. By using a special design of the magnetic circuit, the proposed electromechanical device ensures high force, kinetic energy, and speed for the mobile part of the actuator.
Keywords: Linear alternative current actuator; Thomson coil actuator; Propulsion system; High force; High speed; Ferromagnetic circuit; Eddy current propulsion; Electromechanical device